Digital Humanities and Librarians: A Team-Based Approach to Learning - Hoeve, Casey; Pankl, Lis; Crosby, Mark (Information Science Reference (an imprint of IGI Global), 2016)
This chapter details the development and implementation of an Introduction to Digital Humanities course (ENGL 695) at Kansas State University (K-State). The course originated with a tenure-track professor with a research specialty in British Romantic-period Literature and the digital humanities. In conjunction with a host of librarians at K-State Libraries, a course was developed that drew on both library resources and librarian knowledges and skills. Over the course of the semester, the professor and the students worked closely with librarians in many areas of the library, including public services, technical services and special collections. The result was four innovative and sustainable digital projects that highlighted the resources and research interests at K-State. In addition to introducing students to the digital humanities, the course also served to establish a framework for future initiatives, including hosting a digital humanities symposium and establishing a digital humanities center.